Expression of genes related to glucose metabolism and joint destruction in the development of diabetes mellitus in patients with osteoarthritis - E. V. Chetina; E. P. Sharapova; N. G. Kashevarova; E. A. Taskina; G. A. Markova; L. I. Alekseeva; A. A. Lila (Современная ревматология)
Many patients with osteoarthritis (OA) tend to have comorbidities. This tendency is more frequently observed to increase with age. One of the comorbidities is type 2 diabetes mellitus (T2DM). Due to the higher prevalence of coexistence of these two conditions, it has been suggested that T2DM-associated hyperglycemia may adversely affect joint tissues and increase OA severity. However, the molecular mechanisms in the development of DM in patients with OA remain unclear.Objective: to trace the dynamics of T2DM development in patients with OA at the level of the expression of genes associated with glucose metabolism, joint destruction, and general regulation of metabolic processes.Patients and methods. Three patients with OA were followed up for 4—6 years, including the year of onset of T2DM. The clinical condition of the patients was analyzed once a year. Total RNA was annually isolated from their blood and used to determine the level of gene expression by real-time polymerase chain reaction.Results and discussion. The development of T2DM was shown to be accompanied by the increased expression of genes related to glycolysis, Krebs cycle, pentose phosphate pathway, matrix metalloproteinases and regulators of AMPKand mTOR metabolism. By contrast, the level of the hypoxia regulator HIF1a and hexosamine pathway genes was decreased.Conclusion. The occurrence of T2DM in the presence of OA is likely to be associated with the higher needs for cells for ATP energy and is accompanied by activation of the glucose assimilation pathways, as well as by the increased expression of the genes responsible for extracellular matrix destruction. This may be caused by impaired protein glycosylation due to inhibition of the hexosamine pathway.